Community Oriented Substance Use Programme in the City of Tshwane: A Cross-sectional Survey of Stakeholder Perceptions - Scheibe, Andrew; Ncube, Likwa; Nonyane, Dimakatso; Coetzee-Spies, Magriet; Marcus, Tessa (Southern African Journal of Social Work and Social Development)
The City of Tshwane and University of Pretoria’s Community Oriented Substance Use Programme (COSUP) is an applied research intervention to address drug use-related harms in the city by using a harm reduction community-oriented primary care approach. This is a study of stakeholder perceptions of South Africa’s first publicly funded community-based harm reduction programme. In late 2021, purposively sampled respondents were surveyed using a cross-sectional survey. Electronically captured data were collected on respondent demographic characteristics, familiarity with COSUP and perceptions of COSUP’s effect on service users’ well-being, access to drug use services, family relationships, community integration, and on effective approaches to managing drug use. Frequencies and proportions were analysed as a total and by the degree of familiarity with COSUP, using descriptive statistics. Overall, 338 (93.1%) of the 363 stakeholders who consented to participate in the study had some familiarity with COSUP. Socio-demographically, 68.1% were female and over half (52.4%) were aged between 25–39 years. Most (70–80%) thought COSUP improved client well-being, family relationships and community re-integration. Most (80–84%) perceived COSUP to have increased service provider willingness to support people who use drugs, improved stakeholder networking and raised awareness of drug-related services. Most (76%) considered harm reduction to be the best approach to manage harmful drug use in the city. Stakeholders exposed to the work of COSUP perceive the intervention to be beneficial for individuals, families and service-providing organisations. Most favour a harm reduction approach to drug use and believe COSUP should be sustained and expanded.